2012
DOI: 10.1097/mcp.0b013e3283521066
|View full text |Cite
|
Sign up to set email alerts
|

Update on viral infections in lung transplantation

Abstract: Pharmacological immune suppression, the genetic makeup of the patient as well as concurrent viral infections impact on the successful outcome of lung transplantation and call for more detailed immune-guided diagnostics and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…Des prophylaxies de 12 mois sont préconisées après transplantation du poumon et du grêle. Au-delà, le risque d'infection est moindre mais constant, en particulier chez le transplanté pulmonaire [33] ou multiorganes.…”
Section: L'infection à Cytomégalovirusunclassified
“…Des prophylaxies de 12 mois sont préconisées après transplantation du poumon et du grêle. Au-delà, le risque d'infection est moindre mais constant, en particulier chez le transplanté pulmonaire [33] ou multiorganes.…”
Section: L'infection à Cytomégalovirusunclassified
“…Studies have demonstrated a higher prevalence of SAGs pre-transplant in patients with CF and IPF compared to patients with other conditions such as COPD, whereas other studies have shown this can lead to the expansion of auto-reactive lymphocytes. Individuals with these diseases have the highest prevalence of SAGs pre-LTX compared to patients with other diseases such as COPD and alpha-1 anti-trypsin deficiency (89,(94)(95)(96).…”
Section: Pathophysiology Of Amrmentioning
confidence: 99%
“…On the other hand, it is necessary to highlight the role of this family of viruses in the pathogenesis of lower respiratory tract infections both in the immunocompromised and in the immunocompetent host. In the latter group, the infection usually has an asymptomatic or mononucleosis-like syndrome course but, occasionally, a primary cytomegalovirus (CMV) infection can evolve into more severe organ-specific manifestations [47][48][49][50][51][52]. Furthermore, as previously mentioned, many patients may display a colonisation from herpes viruses and, thus, a positive PCR might not be sufficient to distinguish asymptomatic colonisation from an active infection.…”
Section: Discussionmentioning
confidence: 99%